2014
DOI: 10.7287/peerj.preprints.479v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial genetic structure across a hybrid zone between European rabbit subspecies

Abstract: View the peer-reviewed version (peerj.com/articles/582), which is the preferred citable publication unless you specifically need to cite this preprint.Alda F, Doadrio I. 2014. Spatial genetic structure across a hybrid zone between European rabbit subspecies. PeerJ 2:e582 https://doi.org/10.7717/peerj.582 S p a t i a l g e n e t i c s t r u c t u r e a c r o s s a h y b r i d z o n e b e t we e n E u r o p e a n r a b b i t s u b s p e c i e sT h e I b e r i a n P e n i n s u l a i s t h e o n l y r e g i o n i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…5). This is compatible with the previously described asymmetric genetic introgression between rabbit subspecies: the introgression of Occ on Oca is greater than vice versa (Branco et al 2000, Carneiro et al 2013, Alda & Doadrio 2014). This asymmetric introgression could be attributed to multiple episodes of isolation and contact tracking the climatic changes throughout the Pleistocene, prior to the current contact between the subspecies (Branco et al 2002, Rafati et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…5). This is compatible with the previously described asymmetric genetic introgression between rabbit subspecies: the introgression of Occ on Oca is greater than vice versa (Branco et al 2000, Carneiro et al 2013, Alda & Doadrio 2014). This asymmetric introgression could be attributed to multiple episodes of isolation and contact tracking the climatic changes throughout the Pleistocene, prior to the current contact between the subspecies (Branco et al 2002, Rafati et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the genetic drift, gene flow, and the balance between them can also result in population genetic structure [ 4 , 5 ]. Genetic studies using mitochondrial DNA and microsatellite markers reported as essential genetics tools to explain the population structure at different temporal and spatial scales and the genetic flow among individuals within and between populations [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%